Encuentro de dos maestros renovadores : Juan G. Arintero, O.P., y Miguel de Unamuno / Etelvino González López - González López, Etelvino (1937-)
Separata de: Ciencia Tomista, Tomo 139, n. 448 (mayo-agosto 2012), p. 267-286